EFIKASI DIRI PERAWAT TERHADAP PENERAPAN ASUHAN PERKEMBANGAN (DEVELOPMENTAL CARE) - Armina Armina; Happy Hayati; Nani Nurhaeni (Jurnal Akademika Baiturrahim Jambi, 2018)
The neonatal nursing room in several hospitals in Indonesia has been widely disseminated about the application of developmental care but there are still many nurses who have not applied due to lack of nurse confidence (self efficacy is lacking). This study aims to identify the relationship between self efficacy factors and the application of developmental care by nurses in the neonate care unit. This study used cross sectional study design with 82 samples of nurses in neonate level I, II, III at two hospitals in RSAB Harapan Kita and RSPAD GatotSubroto. The instrument used is self-efficacy questionnaire and Indonesian translation instrument Universe develomental care (UDC). The data of this study were analyzed using bivariate analysis with independent T test. The result of bivariate analysis showed that there was a relationship between the application of developmental care with self efficacy of neonate nurse with p = 0,017. The researcher suggests the institution of nursing services to be able to facilitate the provision of funds and training for increase skill and confidence self nurses in the neonate room.